Rome or Brussels ...? an economist's comparative analysis of the development of the European Community and the aims of the Treaty of Rome - Lewis, W. R. (London : Institute of Economic Affairs, 1971)
This book aims to explore the relationship between economic analysis and the political process where the individual is treated as both a consumer in the market and as an elector in the polling booth.
Bibliography: p. 83.
osc 25/10/2018
Loans
Keywords: European Economic Community countries